2001
DOI: 10.1161/01.str.32.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endogenous Estrogen on Blood Flow Through Carotid Arteries

Abstract: Background and Purpose-Recent evidence suggests that physiological changes in the concentration of endogenous estrogens may influence stroke outcome. The purpose of this study was to determine a menstrual cycle-related profile of blood flow through the carotid arteries and its correlation with estrogen concentration. Methods-The flow velocity and cross-sectional area of the common carotid artery, internal carotid artery (ICA), and external carotid artery (ECA) were measured with duplex Doppler sonography throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 55 publications
6
72
0
1
Order By: Relevance
“…Increased concentrations of endogenous estrogen during normal menstrual cycles were associated with a 15% increase in enddiastolic velocities in the ICAs (15). This change was subsequently shown to be related to a decreased resistance index in the ICAs, signifying decreased cerebrovascular impedance (16).…”
Section: Discussionmentioning
confidence: 92%
“…Increased concentrations of endogenous estrogen during normal menstrual cycles were associated with a 15% increase in enddiastolic velocities in the ICAs (15). This change was subsequently shown to be related to a decreased resistance index in the ICAs, signifying decreased cerebrovascular impedance (16).…”
Section: Discussionmentioning
confidence: 92%
“…varied from woman to woman and cycle to cycle. Based on serial measurements of plasma concentration of sex hormones, we showed that even the standard model of the ovarian cycle in humans, with regular mid-cycle ovulation is inaccurate in predicting the actual plasma hormone concentration 15 . The spread of ovulation across the cycle varies widely, and it is only sometimes possible to determine the subjects' accurate ovulation time by relying on the calendar method alone.…”
Section: Discussionmentioning
confidence: 99%
“…The cycles were counted from the first day of menses and were standardized to a 28-day period as described in our previous study 15 . Table 1 Fluctuations of systolic and diastolic arterial blood pressure (ABP), heart rate (HR), 17-beta estradiol (E2) and progesterone (PG) during the menstrual cycle in 19 young healthy women.…”
Section: Testingmentioning
confidence: 99%
“…23,34 Metabolic Basis of Between-Subject Variability Previous studies show a very similar between-subject variability in healthy young subjects with between-subject coefficient of variation of 16% using the Kety Schmidt technique 1 and of 15% to 20% using various magnetic resonance imaging and positron emission tomography methods. 4 Relative between-subject variability in the present study was B13%.…”
Section: Study Limitationsmentioning
confidence: 92%